2018
DOI: 10.1111/jai.13657
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships for four mullets from the Chilika lagoon, East coast of India

Abstract: Summary Current study provides information on Length–weight relationship (LWR) of four fish species of family Mugilidae i.e., Planiliza macrolepis (Smith, 1846), Chelon parsia (Hamilton, 1822), Osteomugil cunnesius (Valenciennes, 1836) and Valamugil speigleri (Bleeker, 1858) from Chilika Lagoon, East coast of India. Samples were collected during monsoon (July 2016), winter (November 2016) and summer (April 2017) seasons from the fisher's boats inside the lagoon while fishing with screen barrier nets (mesh size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is also worthy of note that full development of digestive system can be linked to the 'K' factor. Kund et al (2011) [44] reported that condition factor of smaller fishes are higher when compared to the large ones due to their edacious feeding nature. Bakare (1970) and Fagade (1979) [42] postulated that the condition factor relatively reduces due to the gradual increase in length.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worthy of note that full development of digestive system can be linked to the 'K' factor. Kund et al (2011) [44] reported that condition factor of smaller fishes are higher when compared to the large ones due to their edacious feeding nature. Bakare (1970) and Fagade (1979) [42] postulated that the condition factor relatively reduces due to the gradual increase in length.…”
Section: Resultsmentioning
confidence: 99%
“…This is because previous studies on Indian species of mullets were mainly based on conventional taxonomy, and identification was mainly based on the personal perceptions of authors. Since the 1950s, most authors who working on mullet taxonomy have (i) provided conflicting opinions and statements regarding the morphology and meristics of the various "species" recorded from India (See Supplementary Table S3), (ii) used diagnostic characters that have subsequently been proved as unreliable for identi-fication (e.g., those that change during ontogenic development-adipose eyelids, types of scales, mandibular angle, third anal fin spine) [22,67], and (iii) erroneously assigned species to various genera [18,22,35,[68][69][70][71], without proper justification.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports on LWR of fishes from Chilika have already been published (Panda et al 2016, Karna 2017, 2018a, 2018b, 2018c, but information for several taxa are still lacking. Here, we report LWR of 37 fish species from Chilika Lagoon in India.…”
Section: Introductionmentioning
confidence: 99%